On determining α s (m Z ) from dijets in e + e − thrust - Miguel A. Benitez; André H. Hoang; Vicent Mateu; Iain W. Stewart; Gherardo Vita (Journal of High Energy Physics)
Abstract We update a previous N3LL′+ O α s 3 $$ \mathcal{O}\left(α_s^3\right) $$ determination of the strong coupling from a global fit to thrust data by including newly available perturbative ingredients, upgrading the renormalization scales to include a fully canonical scaling region, and implementing the log resummation in a way which ensures the integrated cross section is unaffected by the leading 1/Q hadronization power corrections. Detailed discussions are provided concerning the stability of the results under variations of the fit range and the importance of summing up higher-order logarithmic terms for convergence and stability. We show that high-precision results can be achieved even when carrying out a more conservative fit by restricting the dataset to a region which is more clearly dominated by dijet events. This leads to α s (m Z ) = 0.1136 ± 0.0012 with χ 2/dof = 0.86, fully compatible with earlier results using a larger fit range. We also demonstrate that a number of additional effects associated to power corrections have a small impact on this fit result, including modifications to the renormalon substraction scheme for dijet power corrections and the inclusion of three-jet power correction models. The fit is also shown to provide very good agreement with data outside the fit range.